2016
DOI: 10.2139/ssrn.3152139
|View full text |Cite
|
Sign up to set email alerts
|

Work Integrated Learning: A Study of Risk Management by University Lawyers

Abstract: Academic administrator: A person who is a member of university management. Contract risk: Legal risks which are associated with contracts involving the host organisation, student and/or university. Enterprise risk management (ERM): A comprehensive process of managing risks across the university that may affect the achievement of university objectives related to its core activities in learning and teaching, research, and service (refer further section 1.8.5). Financial risk: An event or circumstance that affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…University lawyer experiences of workplace bullying, sexual harassment and poor supervision in the case study are shared by WIL staff and students in many empirical studies, as identified by Cameron (2016). In particular, university lawyer experiences with hazards in the workplace are supported by the survey findings of Cameron and Klopper (2015) in which workplace health and safety was a prominent area of legal work, and considered to be the greatest future legal risk to the university with respect to WIL programs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…University lawyer experiences of workplace bullying, sexual harassment and poor supervision in the case study are shared by WIL staff and students in many empirical studies, as identified by Cameron (2016). In particular, university lawyer experiences with hazards in the workplace are supported by the survey findings of Cameron and Klopper (2015) in which workplace health and safety was a prominent area of legal work, and considered to be the greatest future legal risk to the university with respect to WIL programs.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, university lawyer experiences with hazards in the workplace are supported by the survey findings of Cameron and Klopper (2015) in which workplace health and safety was a prominent area of legal work, and considered to be the greatest future legal risk to the university with respect to WIL programs. The significant number of empirical studies addressing hazardous workplace environments or work practices generally address three events or circumstances: student exposure to diseases in medical practice, most notably needle-stick injuries; physical injury to students caused by workplace equipment; and musculoskeletal injuries suffered by dental students whilst operating workplace equipment (Cameron, 2016). University lawyers expanded the legal risks identified in the empirical studies by describing personal factors of WIL staff, students and host organisations as the cause or consequence of workplace hazards.…”
Section: Discussionmentioning
confidence: 99%
“…The study has its origins at a workshop, during which the lead author presented ten risks in WIL frequently identified by university lawyers as part of his PhD thesis (Cameron, 2016). The lead author subsequently selected the five most frequently cited and/or discussed WIL risks in the workshop as the basis for the research project, which were:…”
Section: Methodsmentioning
confidence: 99%
“…WIL poses risks which, if not appropriately managed, may expose the institution to significant harm and undermine the delivery of WIL placements to students (Cameron, 2016). Developing and executing a robust risk management framework for WIL is not only a wise business strategy but may be a legal necessity.…”
Section: Risk Management In Wilmentioning
confidence: 99%
See 1 more Smart Citation